2023
DOI: 10.1371/journal.pone.0285078
|View full text |Cite
|
Sign up to set email alerts
|

Shaped by the COVID-19 pandemic: Psychological responses from a subjective perspective–A longitudinal mixed-methods study across five European countries

Abstract: Background Contextual factors are essential for understanding long-term adjustment to the COVID-19 pandemic. Therefore, the present study investigated changes in mental health outcomes and subjective pandemic-related experiences over time and across countries. The main objective was to explore how psychological responses vary in relation to individual and environmental factors. Methods The sample consisted of N = 1070 participants from the general population of Austria, Croatia, Georgia, Greece, and Portugal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 83 publications
(105 reference statements)
1
0
0
Order By: Relevance
“…The fluctuations in AD symptoms also differed significantly across individuals. This is in line with a recent study which identified four distinct trajectories of AD [54], highlighting the high variability in people's reactions to the pandemic, as demonstrated earlier [76,77].…”
Section: Trajectories Of Adjustment and Well-beingsupporting
confidence: 91%
“…The fluctuations in AD symptoms also differed significantly across individuals. This is in line with a recent study which identified four distinct trajectories of AD [54], highlighting the high variability in people's reactions to the pandemic, as demonstrated earlier [76,77].…”
Section: Trajectories Of Adjustment and Well-beingsupporting
confidence: 91%
“…Regarding post-pandemic interventions, these remain important as a societal and intergovernmental approach to face the consequences of the pandemic, strengthening the intersectorial delivery and developing their progressive universal delivery without compromising the implementation of specific measures for at-risk populations [28]. Looking at public health policymaking through the lens of social justice would promote social and public health policies that might overcome and prevent the occurrence of some difficulties and iniquities that were lived by some parents during the pandemic [22].…”
Section: Discussionmentioning
confidence: 99%